Creole identity in postcolonial Indonesia - Knörr, Jacqueline, 1960- (Integration and conflict studies, 2014)
Contributing to identity formation in ethnically and religiously diverse postcolonial societies, this book examines the role played by creole identity in Indonesia, and in particular its capital, Jakarta. While, on the one hand, it facilitates transethnic integration and promotes a specifically postcolonial sense of common nationhood due to its heterogeneous origins, creole groups of people are often perceived ambivalently in the wake of colonialism and its demise, on the other. In this book, Jacqueline Knörr analyzes the social, historical, and political contexts of creoleness both at the.